2015
DOI: 10.1016/j.jtcvs.2014.10.096
|View full text |Cite
|
Sign up to set email alerts
|

Does the type of suture technique affect the fluid-dynamic performance of bioprostheses implanted in small aortic roots? Results from an in vitro study

Abstract: Our data show that the type of suture technique can influence bioprosthesis performance and that it is reasonable to assume that this is especially true in small annuli (≤ 21 mm). Thus, to optimize prosthesis performance and reduce the incidence of patient-prosthesis mismatch, the role of the suture technique should not be disregarded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 17 publications
(22 reference statements)
0
14
0
Order By: Relevance
“…This feature, along with an effective sizing strategy, increases the chance of implanting a valve size that meets the hemodynamic requirements of the patient, thereby determining a very low gradient at rest. We implanted the Trifecta by means of a simple interrupted suture, which might have favorably influenced the results …”
Section: Discussionmentioning
confidence: 99%
“…This feature, along with an effective sizing strategy, increases the chance of implanting a valve size that meets the hemodynamic requirements of the patient, thereby determining a very low gradient at rest. We implanted the Trifecta by means of a simple interrupted suture, which might have favorably influenced the results …”
Section: Discussionmentioning
confidence: 99%
“…saline, did not mimic the blood rheology. Indeed, despite the use of saline is widely reported in the literature [28,38,39] it potentially introduces a bias in our findings. Anyway, the mock loop is capable of working with any fluid, including blood.…”
Section: Discussionmentioning
confidence: 84%
“…However, beating heart models are significantly more complex and expensive than classical in vitro platforms, thus often representing an effective but inefficient solution either for the evaluation of devices during their early development phase, or for training/educational purposes. With regard to the in vitro approach involving passive biological samples, the integration of excised structures into mock circulatory loops is currently evolving from the sole use of excised valves, either aortic [18,[26][27][28] or mitral [19,29], toward the design of platforms able to house entire passive hearts [20][21][22]. Indeed, the use of entire heart samples ensures a good preservation of the whole cardiac anatomy and allows the testing and analysis of a wider spectrum of devices.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the fluid-dynamic performance of a bioprosthesis depends on frame design, type and position of the leaflets. 7 , 17 , 30 However, the recent introduction of rapid-deployment valves has highlighted the potential hemodynamic improvements related to the absence of sutures. Clinical studies comparing rapid-deployment and conventional sewed-in aortic heart valves reported differences regarding MPG and EOA, seemingly confirming this positive tendency.…”
Section: Discussionmentioning
confidence: 99%
“… 1 A recently published in vitro study supports this hypothesis. 30 However, in current clinical studies, the influence of the suture technique is still under debate. 29 , 33 …”
Section: Introductionmentioning
confidence: 99%